Curvularides A-E: Antifungal hybrid peptide-polyketides from the endophytic fungus Curvularia geniculata - Porntep Chomcheon (2018)
Five new hybrid peptide-polyketides, curvularides A-E (1-5), were isolated from the endophytic fungus Curvularia geniculata, which was obtained from the limbs of Catunaregam tomentosa. Structure elucidation for curvularides A-E (1-5) was accomplished by analysis of spectroscopic data, as well as by single-crystal X-ray crystallography. Curvularide B (2) exhibited antifungal activity against Candida albicans, and it also showed synergistic activity with a fluconazole drug. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA. Weinheim.